Depressive and anxiety disorders and antidepressant prescriptions among insured children and young adults with congenital adrenal hyperplasia in the United States - Harasymiw, Lauren A.; Grosse, Scott D.; Cullen, Kathryn R.; Bitsko, Rebecca H.; Perou, Ruth; Sarafoglou, Kyriakie (Frontiers in Endocrinology, 2023)
Background: Dysfunction in the hypothalamic-pituitary-adrenal axis has been associated with depressive and anxiety disorders. Little is known about the risk for these disorders among individuals with congenital adrenal hyperplasia (CAH), a form of primary adrenal insufficiency. Objective: We investigated the prevalence of depressive and anxiety disorders and antidepressant prescriptions in two large healthcare databases of insured children, adolescents, and young adults with CAH in the United States. Methods: We conducted a retrospective cohort study using administrative data from October 2015 through December 2019 for individuals aged 4-25 years enrolled in employer-sponsored or Medicaid health plans. Results: Adjusting for age, the prevalence of depressive disorders [adjusted prevalence ratio (aPR) = 1.7, 95% confidence interval (CI): 1.4-2.0, p<0.001], anxiety disorders [aPR = 1.7, 95% CI: 1.4-1.9, p<0.001], and filled antidepressant prescriptions [aPR = 1.7, 95% CI: 1.4-2.0, p<0.001] was higher among privately insured youth with CAH as compared to their non-CAH peers. Prevalence estimates were also higher among publicly insured youth with CAH for depressive disorders [aPR = 2.3, 95% CI: 1.9-2.9, p<0.001], anxiety disorders [aPR = 2.0, 95% CI: 1.6-2.5, p<0.001], and filled antidepressant prescriptions [aPR = 2.5, 95% CI: 1.9-3.1, p<0.001] as compared to their non-CAH peers. Conclusions: The elevated prevalence of depressive and anxiety disorders and antidepressant prescriptions among youth with CAH suggests that screening for symptoms of depression and anxiety among this population might be warranted.